A preparation process for coating layer of gray-bottomed white paperboard
By using multiple coating and drying calendering technology in the coating gray-back white paperboard process, the cross-linking effect of pigment particles and modified starch is used to solve the problem of uneven coating distribution, and the smoothness of the coating and ink absorption performance are improved.
Patent Information
- Application Number
- CN202310780754.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-06-29
AI Technical Summary
In the existing process of coated gray-base white paperboard, the volume of modified starch particles is too large, resulting in uneven coating distribution, affecting the uniformity of the surface strength of the paper.
Through multiple coating combined with drying and calendering technology, using the size difference of the pigment particles, the modified starch cross-links with N-hydroxymethylacrylamide to form small particles, filling between the pigment particles, reducing the coating roughness and improving the ink absorption performance.
It effectively reduces the roughness of the coating, improves the ink absorption performance, ensures the smoothness and gloss of the paperboard, and improves the clarity and resolution of the printing pattern.
Smart Images

Figure CN116892130B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gray-bottom white paperboard, in particular to a preparation process of a coating layer of a gray-bottom white paperboard. Background Art
[0002] Coated white paperboard is made of white paperboard as base paper, with a certain amount of coating evenly coated on the surface. Coated white paperboard is divided into white paperboard with waste pulp and white paperboard without waste pulp. Usually, white paperboard without waste pulp is called white cardboard, and white paperboard with waste pulp is coated on one side according to the different usage of the bottom layer, including coated white paperboard with gray bottom and uncoated white paperboard.
[0003] The coated gray-bottomed white paperboard mainly consists of white paperboard and a coating layer, wherein the white paperboard is generally a multi-layer composite structure. The gray-bottomed coated white paperboard includes a surface layer, a lining layer, a core layer and a bottom layer that have been coated twice to three times, wherein the coated surface layer is a pigment coated on the surface of the base paper, and the coating is composed of pigments, adhesives and a variety of additives, wherein the pigment accounts for more than 80% of the total solids of the coating, and the adhesive accounts for more than 10% of the total solids of the coating. Commonly used adhesives include traditional carboxylated styrene butadiene latex. With the development of technology, part of the carboxylated styrene butadiene latex has been gradually replaced by modified starch, but the modified starch also has the problem of too large overall particle volume, which is not conducive to the uniform distribution of the obtained adhesive in the hair coating, and affects the uniformity of the surface strength of the paper. Summary of the invention
[0004] The object of the present invention is to provide a preparation process for a coating layer of a gray-bottomed white paperboard. The present invention utilizes the difference in pigment particles through multiple coatings, drying and calendering, and the modified starch effectively matches the size and position of the pigment particles, thereby reducing the roughness of the resulting coating while ensuring the ink absorption performance.
[0005] To solve this technical problem, the technical solution of the present invention is: a preparation process of a coating layer of a coated gray-bottom white paperboard, wherein the coated gray-bottom white paperboard comprises a bottom layer, a core layer, a lining layer, a surface layer and a coating layer; the coating layer comprises a first coating layer, a second coating layer and a third coating layer from bottom to top;
[0006] The first coating layer includes a first pigment and an adhesive;
[0007] The first pigment includes heavy calcium carbonate and kaolin, wherein the number ratio of the heavy calcium carbonate particles with a diameter less than 2 μm is 75% to 85%; the number ratio of the kaolin particles with a diameter less than 2 μm is greater than 80%; the total weight of the heavy calcium carbonate and the kaolin is calculated as one hundred parts, wherein the weight ratio of the heavy calcium carbonate to the kaolin is (60 to 70): (30 to 40);
[0008] The second coating layer includes a second pigment and an adhesive;
[0009] The second pigment comprises heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 60% to 75%;
[0010] The third coating layer includes a third pigment and an adhesive;
[0011] The third pigment includes light calcium carbonate;
[0012] The adhesive comprises modified starch and carboxylated styrene-butadiene latex in a mass ratio of (1 to 2):1;
[0013] During the drying and calendering process of the obtained coating, cross-linking occurs between the modified starch dispersed in the coating and the N-hydroxymethyl acrylamide grafted on its surface, and the starch aggregates into particles while forming interconnected channels due to drying.
[0014] Along with calendering, the modified starch particles in the first coating layer, the second coating layer and the third coating layer are deformed and filled between the pigment particles due to the size difference of the pigment particles, and the connected pores are deformed to reduce the surface roughness.
[0015] The preferred process for reducing surface roughness is as follows:
[0016] During the drying process, the modified starch in the coating aggregates into small particles, and at the same time, the evaporation of water in the coating forms interconnected channels from bottom to top;
[0017] During the calendering process, the continuous channels in the coating are contacted with the starch powder by the small particles limiting the pigment particles during the calendering process, and the connecting channels are reduced in the third coating layer during extrusion. The present invention uses short-chain oxidized starch molecules modified by N-hydroxymethyl acrylamide, which is conducive to the cross-linking of starch particles through N-hydroxymethyl acrylamide. The structural formula of N-hydroxymethyl acrylamide is as follows:
[0018]
[0019] The primary alcohols of the glucose units in the treated short-chain starch react to form crosslinks, and N-hydroxymethyl acrylamide has good water solubility and contains carbon-carbon double bonds. The short-chain starch molecules are grafted on the surface, and N-hydroxymethyl acrylamide effectively promotes the spatial network connection between the starches. Stronger chemical bonds are formed between the modified starches, and the binding force between the starch molecules is increased. With the calendering at high temperature, the structural strength of the coating is further enhanced. The reason for the increased strength of the coating structure is that N-hydroxymethyl acrylamide is cross-linked with the surrounding short-chain starch or N-hydroxymethyl acrylamide again with the extrusion deformation at high temperature, thereby further improving the performance of the obtained gray-bottom white paperboard.
[0020] Preferably, the modification method of the modified starch comprises the following steps:
[0021] Step 1: Enzymatic hydrolysis of long-chain starch into short-chain starch;
[0022] Add starch, α-amylase and water into a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a water bath at 40°C to 60°C for 30min to 60min;
[0023] α-Amylase: hydrolyzes the α-1,4-glucosidic bonds in the starch molecular chain, cutting the starch chain into short-chain dextrins, oligosaccharides and a small amount of maltose and glucose, reducing the viscosity of starch.
[0024] In the present invention, enzymatic hydrolysis is used to shorten the chain length of starch molecules for the first time, so that macromolecules are degraded, the steric hindrance of starch is reduced, and the fluidity of the coating is improved. At the same time, the shortened starch chains expose more hydroxyl groups, which is also convenient for further modification of short-chain oxidized starch.
[0025] Step 2, preparing oxidized short-chain starch;
[0026] Disperse the short-chain starch obtained in step 1 in deionized water, with the ratio of short-chain starch to deionized water being 0.5 g: 2 ml;
[0027] Heat in a water bath at 30 to 40° C., adjust the pH value of the short-chain starch-deionized water dispersion system to 9 to 10 with sodium hydroxide, add hydrogen peroxide, stir, and react for 30 to 60 minutes, wherein the volume ratio of hydrogen peroxide to deionized water is (0.5% to 0.8%): 1; the hydroxyl groups of the short-chain starch are oxidized to aldehyde groups or carboxyl groups;
[0028] Step 3: Use hydrochloric acid to adjust the pH value of the reaction system in step 2 to 4 to 5; use deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system in step 2;
[0029] The temperature is raised to 80°C to 85°C, and an initiator ammonium persulfate is added, and the temperature is kept for 30 to 50 minutes to obtain short-chain starch modified by N-hydroxymethyl acrylamide; the mass of the initiator is 0.08% to 0.12% of the mass of the starch in step 1. The present invention uses the direct modification of N-hydroxymethyl acrylamide to form interconnected channels from bottom to top, and the short-chain starch forms small particles during the drying process due to the cross-linking of N-hydroxymethyl acrylamide. Further in combination with calendering, the change in the distance between substances causes the small modified starch particles to be deformed by extrusion, and the distribution of light calcium carbonate particles, heavy calcium carbonate particles and kaolin is coordinated to reduce the size of some interconnected channels formed by the light calcium carbonate particles during the drying process. The interconnected channels formed by the heavy calcium carbonate particles and the heavy calcium carbonate particles and kaolin at the bottom have large size of the surrounded pigment particles and small relative displacement of the surrounding pigment particles, thus forming interconnected channels with small pore size at the top and large pore size at the bottom, which is not only beneficial to the absorption of ink, but also ensures the smoothness and gloss of the surface of the obtained gray-based white paperboard.
[0030] Preferably, the adhesive used in the first coating layer is the first adhesive, the adhesive used in the second coating layer is the second adhesive, and the adhesive used in the third coating layer is the third adhesive, wherein the mass ratio of the carboxylated styrene butadiene latex to the first pigment or the second pigment or the third pigment is 10% to 12%;
[0031] The mass ratios of modified starch to carboxylated styrene butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively, wherein M1<M2<M3. The present invention sets the dosage of modified starch in the first adhesive to the third adhesive respectively, promotes the inner diameter change of the connecting channel to continuously change with the dosage of modified starch during the calendering process, the more the dosage of modified starch is used, the greater the deformation caused by calendering, and the capillary structure for absorbing ink forms an inner diameter from thin to thick from top to bottom, which is conducive to the rapid introduction of ink.
[0032] The present invention also coats the surface of the light calcium carbonate in the third pigment with precipitated barium sulfate, and the surface of the precipitated barium sulfate is modified with KH570. The present invention uses KH570 to improve the oleophilic property of the third coating layer at the top of the obtained coating. The surface of the obtained coating has oleophilic properties, and the paint used for printing and dyeing spreads quickly on the surface of the coating, and the ink in contact with the coating effectively absorbs the ink through the capillary channels in the coating; therefore, the present invention can effectively take into account the smoothness and bulk of the obtained gray-bottomed white paperboard, which is conducive to printing.
[0033] Preferably, the mass of N-hydroxymethyl acrylamide is 10% to 12% of the mass of starch in step 1. The present invention ensures effective grafting of N-hydroxymethyl acrylamide and short-chain starch.
[0034] It is preferred to use an automatic coating machine to evenly coat the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 The present invention provides a first coating layer, a second coating layer and a third coating layer, and utilizes the control of the size and shape of pigment particles to form modified starch microparticles, so that the obtained coating has a capillary structure capable of absorbing ink.
[0035] The preferred baking process conditions are as follows:
[0036] The paper sample is dried at 100° C. to 108° C. for 2 to 4 minutes. The paper sample is preferably calendered using a super calender, and the calendering conditions are 110° C. to 120° C. and a pressure of 1.0 MPa to 1.2 MPa.
[0037] Preferably, the D90 of the light calcium carbonate particles in the third coating layer is 100 nm to 200 nm.
[0038] Preferably, the solid content of the coating is 58% to 63%.
[0039] By adopting the above technical solution, the beneficial effects of the present invention are:
[0040] The hydroxyl groups on the starch molecular chain segments are hydrophilic groups and cannot form a network cross-linked structure when solidified. In the process of mixing with styrene-butadiene latex, the strength of the cross-linked structure formed by the starch molecular chain segments is low, and it is difficult to increase the amount of starch in the modified starch-carboxylic styrene-butadiene latex. In order to overcome the problems existing in the above-mentioned prior art, the present invention utilizes the coordination of pigment particles in the multi-layer structure of the coating to reduce the penetration of moisture in the coating into the surface layer, promotes the volatilization of moisture, and thus forms continuous channels in the coating; at the same time, the N-hydroxymethyl acrylamide in the modified starch is cross-linked with the short-chain starch and itself to form more covalent bonds. With the help of the pressure and temperature of calendering, the small starch particles formed by cross-linking with N-hydroxymethyl acrylamide are squeezed and deformed during the calendering process. During the deformation process, on the one hand, they come into contact with other particles, and on the other hand, the continuous channels originally formed by the evaporation of moisture are displaced due to extrusion to form a continuous capillary structure with fine pores for absorbing ink;
[0041] In order to ensure the formation of the capillary structure, the present invention uses irregularly shaped heavy calcium carbonate and flaky kaolin in the first coating layer. The heavy calcium carbonate has irregular particles due to mechanical crushing and classification, and the particle size is relatively large. The combination with the flaky kaolin limits the downward migration of the coating to a certain extent. The pigment in the second coating layer is heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate. During the drying process, the moisture in the coating first evaporates to form a connecting channel from bottom to top. Since the first coating layer and the second coating layer both use heavy calcium carbonate with larger particle size and flaky kaolin with small specific surface area, and the third coating layer uses light calcium carbonate with smaller particle size and large specific surface area, that is, the dispersion of moisture in the first coating layer and the second coating layer is more concentrated than that in the third coating layer. During the drying process, the moisture evaporates from the bottom to the top. The relatively concentrated volatilization forms a relatively large interconnected channel, and the small particles formed by cross-linking of N-hydroxymethyl acrylamide in the modified starch with the short-chain starch and itself are also distributed on both sides of the channel; subsequently, during the heating and calendering process, the pigment particles are rearranged to a certain extent under the action of pressure, and the short-chain starch forms small particles with certain steric hindrance and self-binding force under the action of N-hydroxymethyl acrylamide, and still maintains the limitation of hard calcium carbonate, kaolin and light calcium carbonate during extrusion, and the deformation of the small particles under pressure is conducive to a smaller distance between the adhesive molecules, and promotes the formation of hydrogen bonds between the adhesive and the surface molecules of the object to be bonded, so that the adhesion is firm; on the other hand, the self-deformation of the small particles of the present invention cooperates with the pressure to make their shapes more irregular and fill them between the pigment particles, thereby ensuring that the migration of the adhesive is reduced and the obtained coating structure is stable;
[0042] The light calcium carbonate and short-chain starch-N-hydroxymethyl acrylamide cross-linked small particles in the third coating layer of the present invention undergo a certain degree of structural collapse surrounding the connecting channels. While collapsing, they are restricted by themselves and other small particles connected to the surrounding areas and the light calcium carbonate particles, thereby forming a refinement at the upper end opening of the connecting channel, ensuring rapid ink absorption while reducing the roughness of the resulting gray-based white paperboard, with clear printed patterns, high resolution and fast transfer speed. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is an infrared spectrum of the modified starch prepared in Example 1 of the present invention;
[0044] Figure 2 It is a schematic structural diagram of the undried coating layer of the gray-bottomed white paperboard coated in the present invention;
[0045] Figure 3 It is a schematic diagram of the structure of the gray-bottomed white paperboard after the coating layer is dried in the present invention;
[0046] Figure 4It is a schematic structural diagram of the coated gray-bottom white paperboard after the coating layer is calendered in the present invention.
[0047] In the figure:
[0048] White paperboard 100 ; coating 200 ; first coating layer 210 ; second coating layer 220 ; third coating layer 230 ; connecting channels 300 ; particles 400 . DETAILED DESCRIPTION
[0049] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.
[0050] Example 1
[0051] This embodiment discloses a method for modifying modified starch coated with a gray-bottom white paperboard coating layer as an adhesive, comprising the following steps:
[0052] Step 1: Enzymatic hydrolysis of long-chain starch into short-chain starch;
[0053] Add starch, α-amylase and water into a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a water bath at 60°C for 60 minutes; the mass ratio of α-amylase to starch is 1 mg:5 g;
[0054] Step 2, preparing oxidized short-chain starch;
[0055] Disperse the short-chain starch obtained in step 1 in deionized water, with the ratio of short-chain starch to deionized water being 0.5 g: 2 ml;
[0056] The solution was heated in a water bath at 40°C, and the pH value of the short-chain starch-deionized water dispersion system was adjusted to 9 by sodium hydroxide. Hydrogen peroxide was added, stirred, and reacted for 60 minutes. The volume ratio of hydrogen peroxide to deionized water was 0.5%:1. The hydroxyl groups of the short-chain starch were oxidized to aldehyde groups or carboxyl groups.
[0057] Step 3: Use hydrochloric acid to adjust the pH value of the reaction system in step 2 to 5; use deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system in step 2;
[0058] The temperature was raised to 85° C., and ammonium persulfate as an initiator was added and kept warm for 50 minutes to obtain short-chain starch modified with N-hydroxymethyl acrylamide; the mass of the initiator was 0.08% of the mass of the starch in step one.
[0059] In this embodiment, the mass of N-hydroxymethyl acrylamide is 10% of the mass of starch in step one.
[0060] The infrared spectrum of the modified starch obtained in this example is as follows Figure 1 shown.
[0061] from Figure 1 It can be seen that the infrared spectrum of the modified starch obtained in this example is at 3338cm -1 The stretching vibration absorption peak of starch-OH appeared at 2926cm -1 The stretching vibration absorption peak of starch-CH2 appeared at 1035cm -1 The stretching vibration absorption peak of starch CO appeared at Figure 1 There are also characteristic peaks of N-hydroxymethyl acrylamide, such as at 1660cm -1 The C=O vibration peak of secondary amide appeared at 1552 cm -1 The bending vibration peak of the secondary amide N—H appeared at , indicating that the present embodiment effectively grafted N-hydroxymethyl acrylamide onto the short-chain starch.
[0062] Example 2
[0063] This embodiment discloses a method for modifying modified starch by coating a gray-bottom white paperboard coating layer as an adhesive, comprising the following steps:
[0064] Step 1: Enzymatic hydrolysis of long-chain starch into short-chain starch;
[0065] Add starch, α-amylase and water into a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a 40°C water bath for 60 minutes; the mass ratio of α-amylase to starch is 1 mg:5 g;
[0066] Step 2, preparing oxidized short-chain starch;
[0067] Disperse the short-chain starch obtained in step 1 in deionized water, with the ratio of short-chain starch to deionized water being 0.5 g: 2 ml;
[0068] The solution was heated in a water bath at 30°C, the pH value of the short-chain starch-deionized water dispersion system was adjusted to 10 with sodium hydroxide, hydrogen peroxide was added, stirred, and reacted for 60 minutes, the volume ratio of hydrogen peroxide to deionized water was 0.8%:1; the hydroxyl groups of the short-chain starch were oxidized to aldehyde groups or carboxyl groups;
[0069] Step 3: Use hydrochloric acid to adjust the pH value of the reaction system in step 2 to 5; use deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system in step 2;
[0070] The temperature was raised to 80° C., and ammonium persulfate as an initiator was added and kept warm for 50 minutes to obtain short-chain starch modified with N-hydroxymethyl acrylamide; the mass of the initiator was 0.12% of the mass of the starch in step one.
[0071] In this embodiment, the mass of N-hydroxymethyl acrylamide is 12% of the mass of starch in step one.
[0072] Example 3
[0073] This embodiment discloses a preparation process of a coating layer of a coated gray-bottom white paperboard, wherein the coated gray-bottom white paperboard comprises a bottom layer, a core layer, a lining layer, a surface layer and a coating layer; the coating layer comprises a first coating layer, a second coating layer and a third coating layer from bottom to top;
[0074] The first coating layer includes a first pigment and a first adhesive;
[0075] The first pigment includes heavy calcium carbonate and kaolin, wherein the weight ratio of the heavy calcium carbonate particles smaller than 2 μm is 75%; the weight ratio of the kaolin particles smaller than 2 μm is 85%; the total weight of the heavy calcium carbonate and the kaolin is calculated as 100 parts, wherein the weight ratio of the heavy calcium carbonate to the kaolin is 60 parts:40 parts;
[0076] The second coating layer includes a second pigment and a second adhesive;
[0077] The second pigment comprises heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 60%;
[0078] The third coating layer includes a third pigment and a third adhesive;
[0079] The third pigment includes light calcium carbonate, wherein the D90 of the light calcium carbonate is 100 nm;
[0080] The first adhesive, the second adhesive and the third adhesive use carboxylated styrene butadiene latex and the modified starch prepared in Example 1, wherein the mass ratio of carboxylated styrene butadiene latex to the first pigment or the second pigment or the third pigment is 12%; the mass ratio of the modified starch to the carboxylated styrene butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively, wherein M1<M2<M3;
[0081] The first coating layer comprises the following substances in parts by mass:
[0082]
[0083]
[0084] The composition of the second coating layer includes the following substances in parts by mass:
[0085] The composition of the third coating layer includes the following substances in parts by mass:
[0086]
[0087]
[0088] Water was added separately and stirred, and the solid content of the obtained coating was 58%.
[0089] like Figure 2 As shown, a first coating layer 210, a second coating layer 220 and a third coating layer 230 are coated on the surface of the white paperboard 100 respectively;
[0090] During the drying and calendering process of the obtained coating 200, the modified starch dispersed in the coating and the N-hydroxymethyl acrylamide grafted on its surface are cross-linked, and the interconnected pores 300 are formed due to drying and the particles 400 are aggregated at the same time;
[0091] Along with calendering, the modified starch particles in the first coating layer 210, the second coating layer 220 and the third coating layer 230 are deformed and filled between the pigment particles due to the size difference of the pigment particles, and the connecting channels 300 are deformed to reduce the surface roughness of the coating.
[0092] The process of reducing the surface roughness in this embodiment is as follows:
[0093] During the drying process, the modified starch in the coating is aggregated into small particles 400, and at the same time, the evaporation of water in the coating forms interconnecting channels 300 from bottom to top, such as Figure 3 As shown;
[0094] During the calendering process, the distance between the materials changes, the small modified starch particles are deformed by extrusion, and the distribution of light calcium carbonate particles, heavy calcium carbonate particles and kaolin is coordinated to reduce the part of the connected channels formed by the light calcium carbonate particles during the drying process. The connected channels formed by the heavy calcium carbonate particles and the heavy calcium carbonate particles and kaolin at the bottom are formed because the surrounding pigment particles are large in size and the surrounding pigment particles have a small relative displacement, thus forming a connected channel 300 with a small pore size at the top and a large pore size at the bottom, such as Figure 4 As shown; it is not only conducive to the absorption of ink, but also ensures the smoothness and glossiness of the surface of the obtained gray-bottomed white paperboard.
[0095] In this embodiment, an automatic coating machine is used to evenly coat the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 .
[0096] The process conditions for baking in this embodiment are as follows:
[0097] Dry at 108°C for 4 minutes. Place the obtained gray paper and white paperboard at a constant temperature and humidity for 24 hours and then measure its surface properties.
[0098] In this embodiment, a super calender is used to calender the obtained paper sample, and the calendering conditions are 120° C. and a pressure of 1.2 MPa.
[0099] Example 4
[0100] This embodiment discloses a preparation process of a coating layer of a coated gray-bottom white paperboard, wherein the coated gray-bottom white paperboard comprises a bottom layer, a core layer, a lining layer, a surface layer and a coating layer; the coating layer comprises a first coating layer, a second coating layer and a third coating layer from bottom to top;
[0101] The first coating layer includes a first pigment and a first adhesive;
[0102] The first pigment includes heavy calcium carbonate and kaolin, wherein the weight ratio of the heavy calcium carbonate particles smaller than 2 μm is 85%; the weight ratio of the kaolin particles smaller than 2 μm is 85%; the total weight of the heavy calcium carbonate and the kaolin is calculated as 100 parts, wherein the weight ratio of the heavy calcium carbonate to the kaolin is 70 parts:30 parts;
[0103] The second coating layer includes a second pigment and a second adhesive;
[0104] The second pigment comprises heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 70%;
[0105] The third coating layer includes a third pigment and a third adhesive;
[0106] The third pigment includes light calcium carbonate, wherein the D90 of the light calcium carbonate is 100 nm;
[0107] The first adhesive, the second adhesive and the third adhesive use carboxylated styrene butadiene latex and the modified starch prepared in Example 1, wherein the mass ratio of carboxylated styrene butadiene latex to the first pigment or the second pigment or the third pigment is 12%; the mass ratio of the modified starch to the carboxylated styrene butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively, wherein M1<M2<M3;
[0108] The first coating layer comprises the following substances in parts by mass:
[0109]
[0110] The composition of the second coating layer includes the following substances in parts by mass:
[0111]
[0112]
[0113] The composition of the third coating layer includes the following substances in parts by mass:
[0114]
[0115] Water was added separately and stirred, and the solid content of the obtained coating was 58%.
[0116] like Figure 2 As shown, a first coating layer 210, a second coating layer 220 and a third coating layer 230 are coated on the surface of the white paperboard 100 respectively;
[0117] During the drying and calendering process of the obtained coating 200, the modified starch dispersed in the coating and the N-hydroxymethyl acrylamide grafted on its surface are cross-linked, and the interconnected pores 300 are formed due to drying and the particles 400 are aggregated at the same time;
[0118] Along with calendering, the modified starch particles in the first coating layer 210, the second coating layer 220 and the third coating layer 230 are deformed and filled between the pigment particles due to the size difference of the pigment particles, and the connecting channels 300 are deformed to reduce the surface roughness of the coating.
[0119] The process of reducing the surface roughness in this embodiment is as follows:
[0120] During the drying process, the modified starch in the coating is aggregated into small particles 400, and at the same time, the evaporation of water in the coating forms interconnecting channels 300 from bottom to top, such as Figure 3 As shown;
[0121] During the calendering process, the distance between the materials changes, the small modified starch particles are deformed by extrusion, and the distribution of light calcium carbonate particles, heavy calcium carbonate particles and kaolin is coordinated to reduce the part of the connected channels formed by the light calcium carbonate particles during the drying process. The connected channels formed by the heavy calcium carbonate particles and the heavy calcium carbonate particles and kaolin at the bottom are formed because the surrounding pigment particles are large in size and the surrounding pigment particles have a small relative displacement, thus forming a connected channel 300 with a small pore size at the top and a large pore size at the bottom, such as Figure 4 As shown; it is not only conducive to the absorption of ink, but also ensures the smoothness and glossiness of the surface of the obtained gray-bottomed white paperboard.
[0122] In this embodiment, an automatic coating machine is used to evenly coat the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 .
[0123] The process conditions for baking in this embodiment are as follows:
[0124] Dry at 105°C for 4 minutes. Place the obtained gray paper and white paperboard at a constant temperature and humidity for 24 hours and then measure its surface properties.
[0125] In this embodiment, a super calender is used to calender the obtained paper sample, and the calendering conditions are 110° C. and a pressure of 1.2 MPa.
[0126] Comparative Example
[0127] The main difference between this comparative example and Example 3 is that the unmodified starch used in the comparative example replaces the modified starch in the adhesive. The process conditions of drying and calendering are the same as those in Example 3.
[0128] The gray-bottomed white paperboards obtained in Examples 3 and 4 and the comparative example were tested for roughness, folding endurance, ink absorbency and interlayer bonding strength before and after calendering, respectively. The test items and reference test standards are as follows:
[0129] The roughness is in accordance with ISO8791-4-2021 standard; the folding endurance is in accordance with ISO2493-1-2021 standard; the ink absorbency is in accordance with GB / T12911 standard; the specific test data are shown in Table 1, Table 2, Table 3 and Table 4.
[0130] Table 1 Changes in roughness of gray-bottomed white paperboard before and after calendering
[0131] project Before calendering After calendering Example 3 1.34μm 0.78μm Example 4 1.36μm 0.76μm Comparative Example 1.41μm 1.38μm
[0132] Table 2 Changes in folding endurance of gray-backed white paperboard before and after calendering
[0133] project Before calendering After calendering Example 3 39 times 51 times Example 4 38 times 50 times Comparative Example 32 times 36 times
[0134] Table 3 Changes in ink absorption of gray-backed white paperboard before and after calendering
[0135]
[0136]
[0137] Table 4 Changes in interlayer bonding strength of gray-bottomed white paperboard before and after calendering
[0138] project Before calendering After calendering Example 3 <![CDATA[167J / m 2 ]]> <![CDATA[182J / m 2 ]]> Example 4 <![CDATA[168J / m 2 ]]> <![CDATA[181J / m 2 ]]> Comparative Example <![CDATA[158J / m 2 ]]> <![CDATA[163J / m 2 ]]>
[0139] In the comparative example, the starch that has not been shortened presents a spiral structure in water, has a large volume, and is difficult to cross-link. It can be seen from Tables 1 to 4 that the starch that is difficult to cross-link is used to make a coating, and its surface is rough, the structural strength is poor, and the performance change before and after calendering is small; in the present invention, the short-chain starch utilizes N-hydroxymethyl acrylamide in the modified starch to cross-link with the short-chain starch and itself to form more covalent bonds, and with the help of the pressure and temperature of calendering, the small starch particles formed by cross-linking with N-hydroxymethyl acrylamide are squeezed and deformed during the calendering process. During the deformation process, on the one hand, they contact with other particles, and on the other hand, the continuous channels originally formed by the evaporation of water are displaced due to extrusion to form a continuous capillary structure with small pore size for absorbing ink; therefore, the roughness, folding resistance, ink absorbency and interlayer bonding strength of the coating obtained before and after calendering are improved.
[0140] In order to ensure the formation of the capillary structure, the present invention uses irregularly shaped heavy calcium carbonate and flaky kaolin in the first coating layer. The heavy calcium carbonate has irregular particles due to mechanical crushing and classification, and the particle size is relatively large. The combination with the flaky kaolin limits the downward migration of the coating to a certain extent. The pigment in the second coating layer is heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate. During the drying process, the moisture in the coating first evaporates to form a connecting channel from bottom to top. Since the first coating layer and the second coating layer both use heavy calcium carbonate with larger particle size and flaky kaolin with small specific surface area, and the third coating layer uses light calcium carbonate with smaller particle size and large specific surface area, that is, the dispersion of moisture in the first coating layer and the second coating layer is more concentrated than that in the third coating layer. During the drying process, the moisture evaporates more concentratedly from bottom to top to form a larger connecting channel. At the same time, the small particles formed by cross-linking of N-hydroxymethyl acrylamide in the modified starch with short-chain starch and itself are also distributed on both sides of the channel. Subsequently, in the process of heating and calendering In the present invention, the pigment particles are rearranged to a certain extent under the action of pressure, and the short-chain starch forms small particles with certain steric hindrance and self-binding force under the action of N-hydroxymethyl acrylamide, and still maintains the limitation of hard calcium carbonate, kaolin and light calcium carbonate during extrusion. The deformation of the small particles under pressure is conducive to a smaller distance between the adhesive molecules, and promotes the formation of hydrogen bonds between the adhesive and the surface molecules of the object to be bonded, so that the adhesion is firm; on the other hand, the self-deformation of the small particles of the present invention cooperates with the pressure to make their shapes more irregular and fill between the pigment particles, so as to ensure that the migration of the adhesive is reduced, and the obtained coating structure is stable; the light calcium carbonate and the short-chain starch-N-hydroxymethyl acrylamide cross-linked small particles in the third coating layer of the present invention undergo a certain degree of structural collapse surrounding the connecting channels, and at the same time, they are limited by themselves and other small particles connected to the surrounding and the light calcium carbonate particles, so as to form a refinement at the upper end opening of the connecting channel, so as to ensure rapid ink absorption while reducing the roughness of the obtained gray-bottom white paperboard, and the printed pattern is clear, the resolution is high and the transfer speed is fast.
Claims
1. A process for preparing a coating layer of a gray-bottomed white paperboard, characterized in that: The coated gray-bottom white paperboard comprises a bottom layer, a core layer, a lining layer, a surface layer and a coating layer; the coating layer comprises a first coating layer, a second coating layer and a third coating layer from bottom to top; The first coating layer includes a first pigment and an adhesive; The first pigment includes heavy calcium carbonate and kaolin, wherein the weight ratio of the heavy calcium carbonate particles with a diameter less than 2 μm is 75% to 85%; the weight ratio of the kaolin particles with a diameter less than 2 μm is greater than 80%; the total weight of the heavy calcium carbonate and the kaolin is calculated as one hundred parts, wherein the weight ratio of the heavy calcium carbonate to the kaolin is (60 to 70): (30 to 40); The second coating layer includes a second pigment and an adhesive; The second pigment includes heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 60% to 75%; The third coating layer includes a third pigment and an adhesive; The third pigment includes light calcium carbonate; The adhesive comprises modified starch and carboxylated styrene-butadiene latex in a mass ratio of (1 to 2):1; During the drying and calendering process of the obtained coating, cross-linking occurs between the modified starch dispersed in the coating and the N-hydroxymethyl acrylamide grafted on its surface, and the starch aggregates into particles while forming interconnected channels due to drying. Along with calendering, the modified starch particles in the first coating layer, the second coating layer and the third coating layer are deformed and filled between the pigment particles due to the size difference of the pigment particles, and the connected pores are deformed to reduce the surface roughness; The modification method of the modified starch comprises the following steps: Step 1: Enzymatic hydrolysis of long-chain starch into short-chain starch; Add starch, α-amylase and water to a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a water bath at 40°C to 60°C for 30min to 60min; Step 2, preparing oxidized short-chain starch; Disperse the short-chain starch obtained in step 1 in deionized water, with the ratio of short-chain starch to deionized water being 0.5 g:2 ml; Heat in a water bath at 30 to 40°C, adjust the pH value of the short-chain starch-deionized water dispersion system to 9 to 10 with sodium hydroxide, add hydrogen peroxide, stir, and react for 30 to 60 minutes, the volume ratio of hydrogen peroxide to deionized water is (0.5% to 0.8%): 1; Step 3: Use hydrochloric acid to adjust the pH value of the reaction system in step 2 to 4 to 5; use deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system in step 2; The temperature is raised to 80° C. to 85° C., and ammonium persulfate as an initiator is added, and the temperature is kept for 30 min to 50 min to obtain short-chain starch modified with N-hydroxymethyl acrylamide; the mass of the initiator is 0.08% to 0.12% of the mass of the starch in step one.
2. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: The process of reducing surface roughness is as follows: During the drying process, the modified starch in the coating aggregates into small particles, and at the same time, the evaporation of water in the coating forms interconnected channels from bottom to top; During the calendering process, the continuous channels in the coating are in contact with the starch powder by small particles limiting the pigment particles during the calendering process, and the connecting channels are reduced during extrusion and are located in the third coating layer.
3. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: The adhesive used in the first coating layer is the first adhesive, the adhesive used in the second coating layer is the second adhesive, and the adhesive used in the third coating layer is the third adhesive, wherein the mass ratio of carboxylated styrene butadiene latex to the first pigment or the second pigment or the third pigment is 10% to 12%; The mass ratios of modified starch to carboxylated styrene-butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively, wherein M1<M2<M3.
4. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: The mass of N-hydroxymethyl acrylamide is 10% to 12% of the mass of starch in step one.
5. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: Use an automatic coating machine to evenly apply the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 .
6. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: The baking process conditions are as follows: Dry at 100℃ to 108℃ for 2min to 4min.
7. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: The obtained paper sample was calendered using a super calender, and the calendering conditions were: Temperature 110℃ to 120℃, pressure 1.0MPa to 1.2MPa.
8. The process for preparing the coating layer of the coated gray-bottom white paperboard according to claim 1, characterized in that: The D90 of the light calcium carbonate particles in the third coating layer is 100 nm to 200 nm.
9. A process for preparing a coating layer of a coated gray-bottom white paperboard according to any one of claims 1 to 8, characterized in that: The solid content of the coating is 58% to 63%.
Citation Information
Patent Citations
White board paper used for coating
CN103184710A
Paint special for paperboard coating and paperboard
CN111379192A